Natural Vascular Scaffolding Treatment Promotes Outward Remodeling During Arteriovenous Fistula Development in Rats - Shiu, Yan-Ting; He, Yuxia; Tey, Jason C. S.; Knysheva, Marina; Anderson, Blake; Kauser, Katalin (Frontiers in Bioengineering and Biotechnology, 2021)
Following creation, an arteriovenous fistula (AVF) must mature (i.e., enlarge lumen to allow high blood flow) before being used for hemodialysis. AVF maturation failure rates are high, and currently, there are no effective therapy to treat this problem. The maturation process is likely affected by the integrity of the vascular extracellular matrix (ECM). Natural Vascular Scaffolding (NVS) Therapy is a new technology that interlinks collagen and elastin via photoactivation of a locally delivered small molecule (4-amino-1,8-naphtalamide). We hypothesized that NVS Therapy may improve AVF remodeling by preserving ECM integrity. AVFs were created in Wistar male rats by connecting the femoral vein (end) to femoral artery (side) in the same limb. Immediately after blood flow was restored to dilate the femoral vein by arterial pressure, a 10 ul-drop of the NVS compound (2 mg/ml) was placed on the anastomosis perivascularly. Following 5-minute incubation, the NVS treated area was exposed to 1-min illumination by 450-nm light. The control group received 10 ul-drop of phosphate buffered saline (PBS) and the same light activation. The skin was closed, and rats were euthanized 4 weeks (n=6-9 per group) post-AVF creation for histology, morphometry, immunohistochemistry, and multiphoton microscopy for second-harmonic-generation evaluation of collagen fibers. The vascular thickness was similar in both groups. The AVF vein’s open lumen area and % open lumen area in NVS-treated rats were significantly larger than in PBS-treated rats (4.2-fold p=0.014 and 2.0-fold p=0.009, respectively). The inflammatory markers IL-6 and MMP-9 in the AVF walls were significantly decreased in the NVS group than the PBS group. Collagen fibers in the vascular wall trended towards perpendicular alignment to the lumen circumference in the NVS-treated AVFs, with more defined shape but less area than in the PBS-treated AVFs. These results indicate that the NVS Therapy exerted changes in collagen, which may influence AVF maturation. Rats tolerated the NVS treatment well, and the lack of cell death by the treatment was confirmed in cell culture experiments. These results suggest that NVS treatment is safe and may have therapeutic potential by facilitating lumen expansion to enhanced AVF maturation in patients.